In vivo covalent cross-linking of cellular actin by the Vibrio cholerae RTX toxin - Fullner, Karla Jean (Oxford University Press, 2000)
Enteric pathogens often export toxins that elicit diarrhea as a part of the etiology of disease, including toxins that affect cytoskeletal structure. Recently, we discovered that the intestinal pathogen Vibrio cholerae elicits rounding of epithelial cells that is dependent upon a gene we designated rtxA. Here we investigate the association of rtxA with the cell-rounding effect. We find that V.cholerae exports a large toxin, RTX (repeats-in-toxin) toxin, to culture supernatant fluids and that this toxin is responsible for cell rounding. Furthermore, we find that cell rounding is not due to necrosis, suggesting that RTX toxin is not a typical member of the RTX family of pore-forming toxins. Rather, RTX toxin causes depolymerization of actin stress fibers and covalent cross-linking of cellular actin into dimers, trimers and higher multimers. This RTX toxin-specific cross-linking occurs in cells previously rounded with cytochalasin D, indicating that G-actin is the toxin target. Although several models explain our observations, our simultaneous detection of actin cross-linking and depolymerization points toward a novel mechanism of action for RTX toxin, distinguishing it from all other known toxins.